ORAL TRADITION OF KOLOLI KIE AS A CULTURAL LEARNING RESOURCE FOR THE ISLAND TERNATE COMMUNITY - Sarmina Ati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
So far, the function of oral tradition is only considered normatively and judged as something static. But with the demands of globalization, the function of oral tradition should have been changed to be practical. One form of oral tradition that is still considered to have values that are still relevant to the needs of community supporters who carried on from generation to generation is a traditional ceremony. One of the traditional ceremonies owned by the people of Ternate is kolie kie. Although in reality only a small part of Ternate people who still hold this ceremony, namely the people who are in the sub-district of Ternate Islands. The content of cultural values and meaning in the tradition of kololi kie can also be a source or medium of cultural learning for the community of the island of Ternate. Real learning is a process of improving a person's cognitive done in the classroom only, can also be obtained by utilizing the environment as a target for learning, learning resources, and learning tools. One of the learning theories that accommodate the demands of sociocultural-revolution or an environment-based learning style is the theory of learning developed by Vygotsky. In Vygotsky's theory, it is argued that the main thing in improving one's mental functions is derived from the social life or group, and not just from the individual himself.